The Influence of Play Method in Enhancing Early Childhood Cooperation Skills at TK Al-Jamiatul Amaliyah Gerumpung - Suhaimi; Syahdan; Kamaruddin (Formad English Foundation NTB-Jakarta, 2024)
The objective of this research is to identify the influence of the play method on the improvement of cooperation abilities in early childhood at Al-Jamiatul Amaliah Gerumpung Kindergarten for the Academic Year 2022/2023. The research method employed a quantitative approach with a pretest-posttest control group design. Data collection techniques included Pretest (Initial Data Collection), Posttest (Final Data Collection), and Assessment Scale. The data analysis conducted by the researcher included Data Description, Preliminary Statistical Tests, Intergroup Comparison Tests, Internal Change Analysis, Play Method Effectiveness Analysis, and Result Interpretation. The research findings indicate that the play method has an influence on the improvement of cooperation abilities. In the control group, the calculated t-value of 0.81 is smaller than the critical t-value of 2.08, indicating no improvement in cooperation abilities before the application of the play method. Meanwhile, in the experimental group, the calculated t-value of 4.75 is greater than the critical t-value of 2.08, signifying that the influence of the play method on enhancing cooperation abilities in early childhood is highly significant and effective.